Risk factor analysis for meralgia paresthetica: A hospital-based study in Taiwan. (September 2017) - Weng, Wei-Chieh; Wei, Yi-Chia; Huang, Wen-Yi; Chien, Yu-Yi; Peng, Tsung-I; Wu, Chia-Lun
Highlights: The causes of meralgia paresthetica vary with different populations and lifestyles. Meralgia paresthetica of male is often in middle age with significant risk factors. The cause of meralgia paresthetica in female is usually obscure. Abstract: Recognizing the cause is essential for the management of meralgia paresthetica (MP), also known as lateral femoral cutaneous neuropathy. The aim of this study was to investigate the etiologies of MP and their influence on each other. This retrospective study enrolled referral patients with electromyographic studies who fulfilled the clinical and electrodiagnostic criteria of MP from January 2003 to December 2013. Data including age, gender, body weight, body height, occupation, and relevant medical history were collected. The etiological analysis was based on age and gender. A total of 50 patients (30 males and 20 females) were enrolled. The average age (±standard deviation) at diagnosis was 49.8 ± 12.8 years. Risk factors were identified in 29 cases (58.0%). More patients younger than 50 years of age were male (73.1%, p  = 0.049). Peaks of age occurred between 41–50 years in men and 51–60 years in women. More males had a body mass index ≥ 24 kg/m 2 (69.2% vs. 31.6%, p  = 0.012) and ≥27 kg/m 2 (34.6% vs. 0.0%, p  = 0.006). Overweight and obese patients were more vulnerable to occupational factors (50.0% vs. 19.0%, p  = 0.030). Only one case had diabetes mellitus (2%). Male middle-aged patients with a higher body mass index and certain occupations had an increased risk of MP. In contrast to the peak age distribution of the male patients, the frequency of developing MP was relatively even among the women at all ages. The cause was often obscure.